1983
DOI: 10.1002/bip.360220166
|View full text |Cite
|
Sign up to set email alerts
|

Some novel approaches to the design and synthesis of peptide–catecholamine conjugates

Abstract: SynopsisA series of novel, functionalized catecholamines (congeners) has been synthesized in which, formalistically, the N-isopropyl group of isoproterenol has been extended by a linear alkyl chain of varying length, terminated by a carboxyl group. Model amide derivatives have also been prepared in order to optimize the biological activity of these derivatives and also to aid in the design of appropriate peptides for the synthesis of conjugates. As a result of these studies, a series of amino acid and monodisp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

1983
1983
2016
2016

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 13 publications
0
18
0
Order By: Relevance
“…A novel series of p-aminophenylalanine-based peptide conjugates of previously-described N-carboxylic acid congeners of norepinephrine (9) has been prepared. The fact that the peptide carriers were completely monodisperse and varying in size from a single, blocked amino acid to pentapeptides has permitted complete characterization of the peptide carriers and conjugates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A novel series of p-aminophenylalanine-based peptide conjugates of previously-described N-carboxylic acid congeners of norepinephrine (9) has been prepared. The fact that the peptide carriers were completely monodisperse and varying in size from a single, blocked amino acid to pentapeptides has permitted complete characterization of the peptide carriers and conjugates.…”
Section: Discussionmentioning
confidence: 99%
“…p-Nitro-D-phenylalanine (6.20 g, 29.5 mmol) was acetylated with acetic anhydride (9 ml) in aqueous sodium hydroxide at pH 9 …”
Section: Nol-acetyl-pnitro-d-phenylalaninementioning
confidence: 99%
“…Thousands of such microarrays can be made from a single OBOC library. 10 Thus, a single peptoid library could be used to couple with a large number of different lead molecules, providing a route the rapid isolation of higher affinity ligands for a large number of proteins. Such efforts are underway.…”
mentioning
confidence: 99%
“…Previous in vitro studies have shown that 119 and 143 are orders of magnitude more potent than ISO in the stimulation of cyclic adenosine monophosphate (cAMP) accumu lation in S49 mouse lymphoma cells [1][2][3][4][5] and that 143 is a more potent positive ino tropic agent than ISO as measured in an iso lated guinea pig atria preparation [2,5], In addition, in this preparation, 143 appeared to have preferential inotropic versus chrono tropic effects. The inotropic effect of 143 also persisted much longer than that ob served with ISO.…”
Section: Introductionmentioning
confidence: 99%
“…In vivo, 143 (i.v.) was shown to be more potent than ISO in the reduction of blood pressure in anesthetized rats [2][3][4][5], The ED50 values were found to be 1.44 X 10'9 mol/kg for 143 (0.78 pg/kg), 8.25 X 10'9 mol/kg for 119 (3.99 pg/kg), and 7.54 X 10-9 mol/kg for ISO (1.87 pg/ kg). Following intravenous administration to anesthetized dogs [4,5], the positive ino tropic response produced by 143 lasted 100 min, compared to the 2-3 min response observed with ISO at four times the molar dose.…”
Section: Introductionmentioning
confidence: 99%